Conventional water bath heating on undried brewer's spent grain: Functionality, fatty acids, volatiles, polyphenolic and antioxidant properties - Naibaho Joncer; Pudło Anna; Bobak Łukasz; Wojdyło Aneta; López Álvaro Alemany; Pangestika Leonie Margaretha Widya; Andayani Safira Noor; Korzeniowska Małgorzata; Yang Baoru (Elsevier Ltd, 2025)
Brewers' spent grain (BSG) contains bioactive compounds. It was hypothesized that heating treatments using conventional water bath heating (CWH) on brewers' spent grain (BSG) would modify the functionality, chemical constituents and antioxidant activities of BSG. Different temperatures and time exposures (80, 90 and 100 °C at 15, 30 and 60 min) were applied on fresh undried BSG. CWH at 80 °C increased the amount of flavan-3-ols, while 100 °C at 30 and 60 min improved the ABTS (2,2′-Azinobis-(3-ethylbenzthiazoline-6-sulfonic acid) value. CWH significantly declined saturated fatty acid and enhanced the poly-unsaturated fatty acid. Moreover, CWH discharged pungent, floral, spice and mushroom odor perceptions and formed fruity, sweet and pleasant odor perceptions, as well as essential-oil-related compounds. Additionally, CWH improved water-holding and oil-holding capacities. In conclusion, CWH as a low-cost treatment improved the functionality, fatty acid composition and aromatic profile of BSG